Molecular and immunohistochemical characterisation of mesothelioma of the tunica vaginalis*. Issue 1 (10th May 2022) - Anderson, William J; Sholl, Lynette M; Fletcher, Christopher D M; Schulte, Stephanie; Wang, Li Juan; Maclean, Fiona M; Hirsch, Michelle S
Abstract : Aims: Malignant mesothelioma (MM) of the tunica vaginalis (TV) is a rare and aggressive tumour, and the molecular features and staining profile with contemporary immunohistochemical (IHC) biomarkers are largely unexplored. We characterise the clinicopathological, molecular and IHC features of MM ( n  = 13) and mesothelial neoplasms of uncertain malignant potential (MUMP) ( n  = 4). Methods and results: Targeted next‐generation sequencing was performed on seven MMs and two MUMPs. IHC was performed for methylthioadenosine phosphorylase (MTAP), BRCA1‐associated protein 1 (BAP1) and SRY‐box transcription factor 6 (SOX6). Thirteen adenomatoid tumours were also assessed with SOX6. MM were epithelioid (seven of 13) or biphasic (six of 13). In MM, NF2 (five of seven; 71%), CDKN2A (three of seven; 43%) and BAP1 (two of seven; 29%) were most frequently altered. Non‐recurrent driver events were identified in PTCH1 and TSC1 . In contrast, none of these alterations were identified in MUMPs; however, one MUMP harboured a TRAF7 missense mutation. By IHC, loss of MTAP (two of 12; 17%) and BAP1 (two of nine; 22%) was infrequent in MM, whereas both were retained in the MUMPs. SOX6 was positive in nine of 11 (82%) MMs and negative in all MUMPs and adenomatoid tumours. Conclusions: Testicular MM exhibit a similar mutational profile to those of the pleura/peritoneum; however, alterations in CDKN2A and BAP1 are less common. These findings suggest that although MTAP and BAP1 IHC are specific for MM, their sensitivity in testicular MMs appears lower. In addition, rare tumours may harbour targetable alterations in driver genes ( PTCH1 and TSC1 ) that are unusual in MMs at other anatomical sites. SOX6 is sensitive for MM; accordingly, the presence of SOX6 expression argues against a benign neoplastic process. Abstract :